Visitors' satisfaction of visit and the economic impacts of perceptions of ecotourism development support in Alamout area, Iran - Asadi, Azita; Mohd, Abdullah; Fathizahraei, Majid (Universiti Putra Malaysia Press, 2015)
Economic impacts are the main factor in developing sustainable ecotourism. They provide alternatives for the local community to support their lives in addition to traditional farming. Several research studies have focused on local perceptions upon tourism development impacts, but visitors' opinions have received less consideration. This study, therefore, is focused on visitors' perceptions and their intention to support ecotourism development in the Alamout area in Iran. A survey was conducted to assess the visitors' perception, intention to revisit and their support for ecotourism development. The structural equation modelling was developed by using AMOS to analyse the data. The result of the study indicates that "Create jobs", "Economic benefits to residents" and "Employment opportunity" were the high agreed positive economic impacts while "Increase the real estate prices", "Attract non-local investors" and "Increase in the price of goods" were the high negative perceived impacts from visitors' view. Results of the confirmatory factor analysis confirmed that visitors who perceived negative economic impacts were less likely to revisit or recommend the area.